2022
DOI: 10.1101/2022.01.17.476616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-routing metabolism by the mitochondrial pyruvate carrier inhibitor MSDC-0160 attenuates neurodegeneration in a rat model of Parkinson’s disease

Abstract: Background: A growing body of evidence supports the idea that mitochondrial dysfunction might represent a key feature of Parkinson's disease (PD). Central regulators of energy production, mitochondria are also involved in several other essential functions such as cell death pathways and neuroinflammation which make them a potential therapeutic target for PD management. Interestingly, recent studies related to PD have reported a neuroprotective effect of targeting mitochondrial pyruvate carrier (MPC) by the ins… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…In further support of the importance of pyruvate metabolism in affecting PD pathology, Mallet et al (2022) have recently demonstrated that treatment with MSDC-0160 treatment improved motor behavior, decreased dopaminergic denervation, and reduced mTOR activity and neuroinflammation in the unilateral 6-OHDA rat model of PD. Metabolomic analysis indicated that reprogramming pyruvate metabolism increased ketogenesis, beta oxidation and glutamate oxidation and that multiple downstream pathways were likely involved in the beneficial effects.…”
Section: Overviewmentioning
confidence: 88%
“…In further support of the importance of pyruvate metabolism in affecting PD pathology, Mallet et al (2022) have recently demonstrated that treatment with MSDC-0160 treatment improved motor behavior, decreased dopaminergic denervation, and reduced mTOR activity and neuroinflammation in the unilateral 6-OHDA rat model of PD. Metabolomic analysis indicated that reprogramming pyruvate metabolism increased ketogenesis, beta oxidation and glutamate oxidation and that multiple downstream pathways were likely involved in the beneficial effects.…”
Section: Overviewmentioning
confidence: 88%
“…Understanding the metabolic plasticity of brain function in molecular detail has profound clinical implications for human physiology. Indeed, metabolic reprograming through MPC inhibition has emerged as an insulin sensitizing strategy for treatment of type II diabetes and has been shown to attenuate neurodegeneration in some Parkinson's disease models 19,20 . Given our finding that mitochondrial pyruvate uptake regulates synaptic transmission, it is critical to elucidate the short-term or long-term effects of MPC-modulating drugs on cognitive function in healthy individuals and patients suffering from metabolic and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological importance of MPC is further highlighted by its implication in several human pathologies, including cancer, cardiac hypertrophy, diabetes, and microcephaly 18 . Furthermore, there is also growing interest in targeting MPC for treatment of neurological disorders such as Parkinson's disease 19,20 . However, few studies have examined MPC function in the nervous system 21,22 , particularly in the metabolic control of synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%